Collier, Donald: Cultural chronology and change as reflected in the ceramics of the Virú Valley, Perú. Fieldiana: Anthropology, Vol. 43. Chicago Natural History Museum. 226 pp., con 72 figs. en el texto. Chicago, 1955. - Schobinger, Juan (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Arqueología y Etnología, 1956)

(untitled)
Fil: Schobinger, Juan. Universidad Nacional de Cuyo. Facultad de Filosofía y Letras